Extended red aurora associated with super substorm igniting the October 10, 2024 magnetic storm as revealed by citizen science - Ryuho Kataoka; Shinya Nakano; Shiori Uchino; Sachin A. Reddy (Earth, Planets and Space)
Abstract A large magnetic storm occurred on October 10, 2024 and a super substorm occurred just after the shock arrival at 1520 UT. As a result, red auroras were photographed at multiple points over a wide region of Japan from 1700 UT (1 Japan local time). We apply a Bayesian analysis to estimate the time variation of the most probable height and latitude of the red aurora based on the citizen science data set, in combination with the POES/MetOp satellite data sets of electron precipitation boundary. We find that the top height of red aurora extended to ~ 950 km and the red aurora shifted toward low latitude according to the storm development. The ultra-high altitude of the red aurora can be evidence of rapid atmospheric heating and atmospheric expansion. Graphical abstract